Réponses

  • Utilisateur Brainly
2014-10-27T14:25:39+01:00
Développer :

(4x + 1)(4x + 1) - (3x - 2)(4x + 1)
= 16x² + 8x + 1 - (12x² + 3x - 8x - 2)
= 16x² + 8x + 1 - 12x² - 3x + 8x + 2
= 4x² + 13x + 3

Factoriser :

(4x + 1)(4x + 1) - (3x - 2)(4x + 1)
= (4x + 1)(4x + 1 - 3x + 2)
= (4x + 1)(x + 3)

Pour x = - 3 :

(4 x (- 3) + 1)(- 3 + 3)
= (- 12 + 1) x 0
= - 11 x 0
= 0

Pour x = 2 :

(4 x 2 + 1)(2 + 3)
= (8 + 1) x 5
= 9 x 5
= 45
2014-10-27T14:28:36+01:00
E =(4x+1)(4x+1) -(3x-2)(4x+1)

developper
e =(4x+1)(4x+1) -(3x-2)(4x+1)
e =16x²+4x+4x+1 -12x²-3x+8x+2
e =  4x² +13x +3

factorise
e =(4x+1)(4x+1) -(3x-2)(4x+1)
e = (4x+1)(4x+1-3x+2)
e = (4x+1)(x+3)

calculer pour
x = -3
e = (4x+1)(x+3)
e = (4*-3 +1) (-3+3)
e = (-12+1) (0)
e = 0

pour x = 2
e = (4x+1)(x+3)
e =(4*2+1)(2+3)
e = 9*5
e = 45